Social Harmony in Plural Society (Study of Social Integration Post Poso Conflict) - Ruagadi, Henry Anderson; Nursinah, Nursinah; Bunga, Nurfhin Ilma; Pelima, Joice Noviana; Taariwuan, Silvany A. (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
The Poso conflict, which occurred from the late 1990s to the early 2000s, had a significant social impact on the local community. This study aims to explore the social integration process that took place post-conflict in Poso, Central Sulawesi, focusing on the social harmony created within the plural society. A qualitative approach was used to delve into the experiences, views, and social practices of people from different ethnic, religious, and cultural backgrounds in their efforts to rebuild communal life. Data were obtained through in-depth interviews with various parties, including community leaders, religious leaders, and ordinary citizens who directly experienced the conflict and reconciliation process. The findings show that post-conflict social harmony in Poso was achieved through several key steps, including inter-community dialogue, joint activities involving various community groups, and the active role of religious leaders and local leaders in promoting peace. Additionally, support from the government and non-governmental organizations (NGOs) in the form of rehabilitation and reconciliation programs strengthened social integration efforts. This study found that although there were challenges in the reconciliation process, such as distrust and past trauma, consistent efforts to build communication and cooperation between groups successfully created a more harmonious environment. This study provides important insights into the significance of participatory and inclusive approaches in addressing social conflicts and building sustainable integration in plural societies. In conclusion, social harmony in Poso can serve as a model for other regions experiencing similar conflicts, emphasizing the importance of dialogue, cooperation, and the active role of all parties in achieving sustainable peace.